Impact of off-balance sheet activities on bank profitability: Evidence from Bangladesh - Ahmed, Md. Adnan; Rozario, Karin Paulina (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study explores the role of off-balance sheet (OBS) activities in enhancing bank profitability in Bangladesh. In this emerging economy, banks increasingly rely on such exposures to diversify revenue streams. Despite their growing significance, the impact of OBS activities—such as loan commitments, guarantees, and derivatives—on profitability remains underexplored in similar contexts. Methods: Using a panel dataset of Bangladeshi banks, the study employs Generalized Least Squares (GLS) and Panel Corrected Standard Errors (PCSE) models to address key methodological challenges, including heteroskedasticity and cross-sectional dependency. These techniques ensure robust and reliable findings. Results: The findings reveal a positive and statistically significant relationship between OBS activities and bank profitability, emphasizing their role in enhancing financial performance without increasing balance sheet risks. This relationship holds even after controlling for factors such as bank age, credit risk, lending practices, bank size, GDP growth, and the COVID-19 pandemic. Limitations: The study focuses on a single emerging economy, which may limit the generalizability of the findings. Additionally, the dataset spans a specific period, restricting insights into long-term effects. Contribution: This research contributes to the limited literature on OBS activities in emerging markets, providing valuable insights for bank managers and policymakers. Managers can leverage OBS activities to boost profitability, while regulators must maintain oversight to ensure financial stability. The study also offers a foundation for future research on long-term dynamics and cross-country comparisons.